ESTABLISHMENT OF ADVENTITIOUS ROOT CULTURE FROM CELL SUSPENSIONS OF WITHANIA SOMNIFERA (L.) DUNAL: AN IN VITRO APPROACH FOR PRODUCTION OF WITHANOLIDES - CHANDRASEKARAN THILIP; CHELLAPPAN SOUNDAR RAJU; KANDHAN VARUTHARAJU; ABUBAKKER ASLAM; APPAKAN SHAJAHAN (International Journal of Pharma and Bio Sciences, 2015)
Withanolides are a group of naturally occurring steroidal lactones present in roots and leaves of Withania somnifera (L.) Dunal. Withanolides possesses a wide range of pharmacological activities including anticancer to treat various neurodegenerative disorders such as Alzheimer’s, Parkinson’s and Huntington’s diseases. In recent years, several pharmacological studies have been conducted to utilize W. somnifera and several patents have been filed on the therapeutic values of withanolides. Under natural conditions, W. somnifera possesses low levels of withanolides and in vitro culture techniques along with metabolic engineering could be an attractive tool for solving this problem. In the present study, we have induced adventitious roots from cell suspension culture of W. somnifera for the production of withanolides. Half strength MS liquid medium containing 0.5 mg l-1 IBA in combination with 0.25 mg l-1 IAA showed higher production of adventitious roots from cell suspension culture after 4 weeks. Dark condition and 3 % sucrose favored biomass productivity. The outcome of the present study shows great potential of adventitious root culture for large scale production of withanolides.